The Design of Temperature and Soil Humidity Control with Fuzzy Method on Greenhouse for Red Chilli Pepper Seedling - Anton Hidayat Hidayat; - Nasrullah; Darma Putra; - Ramiati (JOIV : International Journal on Informatics Visualization, 2019)
The ideal soil temperature and humidity in red chilli pepper seedling is very important in the growth of the plant. The cultivation of red chili plants in greenhouses is very good, because the environment in greenhouses can be manipulated according to the needs of the plants. The ideal temperature for red chili breeding is 25oC to 27oC, for soil moisture drainage and aeration must be maintained during growth. Red pepper plants can grow well in moisture 50% to 70%, irregular soil moisture can cause rooting disease and root decay in plants. Cultivation of plants in greenhouses can maintain the nursery process, because the plants can be cultivated in accordance with the Operational Procedure Standards (SOP). Generally the farmers in breeding of red pepper is done in a trational way. In the process of temperature control and soil moisture using fuzzy method where the system can work automatically, which can facilitate the work of farmers in seeding plants from uncertain environmental conditions outside. In the measurements that have been done can be taken conclusion percentage error mean temperature from setpoint which have been set at the time in the morning equal to 2,48%, at noon equal to 9,79% and at night equal to 1,93%. Then each addition of 1 second watering, soil humidity rise up to 0.067%.